Field Displacement of Aflatoxigenic Aspergillus flavus Strains Through Repeated Biological Control Applications - Weaver, Mark A.; Abbas, Hamed K. (Frontiers in Microbiology, 2019)
A popular pre-harvest strategy to mitigate aflatoxin contamination of corn involves field application of non-aflatoxigenic strains of Aspergillus flavus. The basis of this biological control may involve multiple factors, but competitive displacement of aflatoxigenic strains by the biocontrol strains is a likely mechanism. Three biocontrol strains (NRRL 21882, 18543 and 30797) were applied annually, over a four-year period, to the same 3.2 ha commercial corn field in the Mississippi Delta, where we monitored their post-release establishment, spread and persistence. Within two months of the first biocontrol application, the percentage of soil-inhabiting aflatoxigenic A. flavus strains in some plots was reduced from 48% to 9% of the population. The frequency of aflatoxigenic A. flavus strains was also significantly reduced in the rest of field. After four years, neighboring plots that had never received a biocontrol treatment, and distanced from our treatment plots by at least 20 meters, had less than 20% aflatoxigenic isolates. This significant halo effect might be attributed to movement of soil through tillage operations, but the aflatoxigenicity shift could be detected in the untreated plots within two months of the initial applications, at a time when there was no tillage. The A. flavus populations that colonized the grain were also monitored and found to be less than 15% toxigenic in the fourth year for all treatments. Over all treatments and years, less than 2 ppb of aflatoxin was detected, which could be a consequence of the field-wide shift of the inherent A. flavus population to predominately non-aflatoxigenic strains. This study supports the efficacy of using non-aflatoxigenic A. flavus strains as pre-harvest biocontrol, and shows that most of its effectiveness occurs with the first application.